USE IRAP AND IPBS MOLECULAR MARKERS FOR GENETIC ANALYSIS OF WHEAT VARIETIES - Tagimanova , D.S.; Alzhanova , A.; Khapilina , O.N.; Kalendar , R.N. (Eurasian Journal of Applied Biotechnology, 2014)
Improving the efficiency of the breeding process is now greatly achieved by using molecular markers. Such an approach to the analysis of the breeding material allows the early stages breeding to identify variation at the genetic level, to select variants breeding lines with the necessary features to analyze the DNA of plants. Methods of molecular marking offer great opportunities to improve the efficiency of the breeding, problem solving somaclonal variability. Molecular markers can detect molecular genetic changes in the tissue level of individual plants, and at the cellular level. Each type of molecular markers has its own features, limitations and field of application that must be considered when choosing the most reliable and simple methods of genetic certification of wheat varieties. Molecular markers are now widely used to assess the intraspecific diversity of plants, allow the identification of varieties, species, help secure copyrights breeders allow to study the phylogenetic relationships. Many molecular markers are highly informative, well-reproduced, reliable in determining the individual characteristics of the genotype. Selection of molecular genetic markers to create a genetic passport, determine the genealogical relationships between varieties, as well as marking the major genes of agronomic traits is an urgent task breeding of crop plants.